Highlights on Cerebral Arteriovenous Malformation Treatment Using Combined Embolization and Stereotactic Radiosurgery: Why Outcomes are Controversial? - Sackey, Faustina N A (Cureus, 2017)
Cerebral arteriovenous malformations (AVMs) are abnormal tangling between brain arteries and veins causing an arteriovenous shunt called nidus with an intervening network of vessels from the region of formation and spans through the brain. AVM effect is debilitating to the affected individual due to associated persistent intracerebral hemorrhage, resulting in significant occurrences of seizures and neurological damage. Recent innovative treatments involve a combination of embolization (Embo) procedures followed by stereotactic radiosurgery (SRS), designed to optimize less-invasive practice for the obliteration of the AVMs. Three groups of investigators reported different outcomes based on obliteration rates and adverse events, making the effectiveness of options for therapy, controversial. We have taken the case-oriented-approach to highlight on varying outcomes from various studies and provide insights as to why findings from different operation settings could be so conflicting. We chose 18 articles for systematic analysis based on initial electronic database selection of 40 key papers already identified for inclusion, followed by independent blinding assessment by two co-authors. Our evaluation was based first on our specific inclusion criteria, examining method quality, obliteration rates, serious adverse events (SAEs) and mortality rates. Second, we made a comparison between SRS or embo alone treatments versus combined embo/SRS procedures, relative to AVM sizes, following Spetzler-Martin (SM) method. Third, we considered publications which had concrete statistics with well-defined P-values and clarified outcomes for accurate evaluation. We found that patients with small to medium-sized AVM were susceptible to either embo alone or SRS alone treatments, yielding obliteration rates from 71%-100%. Except for one report, giant sizes AVMs were not amenable to these single treatments, subjecting patients to embo/SRS procedures, which yielded mixed results: One group reported 52%-65% obliteration rates, compared to 23%-28% embo alone treatment. A second group contradicted this apparent beneficial outcome, obtaining obliteration rates of 53% with combined treatment compared to 71% with SRS alone, four-year postoperative. A third group reported there was no difference between single and combined treatments and obtained complete obliteration of 70%-82%, ranging from three-five-years postoperative follow-up. In all the cases analyzed, obliteration rates improved with time. SAEs, such as persistent hemorrhage and permanent neurologic deficits (P-NDs), as well as mortality, were minimal during intraoperative and postoperative follow-ups. The problem of conflicting outcomes in combined treatments of AVM by EMBO/SRS exists. Previous investigators, however, have overlooked to address this issue satisfactorily. Our analysis found that the reported inconsistencies in AVM treatment outcomes are attributable to key factors making therapy unpredictable, which includes: the size of the AVM, nidus localization and accessibility of either Embo or radiation dose applied, certain Embo materials lowering obliteration rates by masking radioactive effect on the nidus during SRS and follow-up timing for obtaining obliteration rates determine the extent of obliteration. We have indicated critical factors which require consideration when planning strategies for treatment of AVM patients and have made suggestions of how to overcome such hurdles.